2023
DOI: 10.1177/22799036231160624
|View full text |Cite
|
Sign up to set email alerts
|

Patient income level and health insurance correlate with differences in health care utilization during the COVID-19 pandemic

Abstract: Background: With the coronavirus outbreak of 2019 (COVID-19) came many changes in how health care is accessed and delivered. Perhaps most notable is the massive expansion of telemedicine, especially in the developed world. With pandemic-induced economic and health care system disruptions, it is reasonable to expect changes in how health care services are utilized by different patients. We examined how health care service usage trends changed for various patient demographics from the pre-COVID-19 era to the COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The COVID-19 pandemic strained health care systems worldwide and altered patient access to care. Systematic reviews of multinational evidence found a nearly universal decline in in-person outpatient health care use in the pandemic’s early stages, but a marked increase in the use of telehealth . Many of these prior health care utilization studies were population-level comparisons of health care use before and during the pandemic rather than comparisons of COVID-19–infected and uninfected cohorts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic strained health care systems worldwide and altered patient access to care. Systematic reviews of multinational evidence found a nearly universal decline in in-person outpatient health care use in the pandemic’s early stages, but a marked increase in the use of telehealth . Many of these prior health care utilization studies were population-level comparisons of health care use before and during the pandemic rather than comparisons of COVID-19–infected and uninfected cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews 1 , 2 , 3 of multinational evidence found a nearly universal decline in in-person outpatient health care use 4 in the pandemic’s early stages, but a marked increase in the use of telehealth. 5 , 6 , 7 , 8 Many of these prior health care utilization studies were population-level comparisons of health care use before and during the pandemic rather than comparisons of COVID-19–infected and uninfected cohorts. This confounds individual-level effects of COVID-19 on health care use with the pandemic’s systemic effects on health care delivery.…”
Section: Introductionmentioning
confidence: 99%